2002
DOI: 10.1073/pnas.232568499
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for CREB-binding protein and p300 in hematopoietic stem cell self-renewal

Abstract: Hematopoietic stem cells (HSC) are tightly regulated through, as yet, undefined mechanisms that balance self-renewal and differentiation. We have identified a role for the transcriptional coactivators CREB-binding protein (CBP) and p300 in such HSC fate decisions. A full dose of CBP, but not p300, is crucial for HSC self-renewal. Conversely, p300, but not CBP, is essential for proper hematopoietic differentiation. Furthermore, in chimeric mice, hematologic malignancies emerged from both CBP ؊/؊ and p300 ؊/؊ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
199
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(215 citation statements)
references
References 26 publications
10
199
1
Order By: Relevance
“…The results are consistent with recent publications suggesting nonredundant roles for CBP and p300 in cell growth, differentiation and development, in spite of their high degree of homology (Kawasaki et al, 1998;Yao et al, 1998;Kung et al, 2000;Yamauchi et al, 2002;Roth et al, 2003). Rebel et al (2002), using a hematopoietic stem cell (HSC) model, concluded that CBP but not p300 is essential for HSC self-renewal, whereas p300 is critical for proper hematopoietic differentiation. Kawasaki et al (1998) found that p300, but not CBP, is absolutely required for RAinduced F9 differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…The results are consistent with recent publications suggesting nonredundant roles for CBP and p300 in cell growth, differentiation and development, in spite of their high degree of homology (Kawasaki et al, 1998;Yao et al, 1998;Kung et al, 2000;Yamauchi et al, 2002;Roth et al, 2003). Rebel et al (2002), using a hematopoietic stem cell (HSC) model, concluded that CBP but not p300 is essential for HSC self-renewal, whereas p300 is critical for proper hematopoietic differentiation. Kawasaki et al (1998) found that p300, but not CBP, is absolutely required for RAinduced F9 differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Mice with monoallelic loss of CBP have defects in bone marrow cellularity and hematopoietic lineage differentiation and display an age-dependent increase in hematopoietic malignancies (Kung et al, 2000). HSC numbers, as estimated by whole bone marrow transplantation assays, are reported to decrease in old Cbp þ /À mice relative to young mice (Rebel et al, 2002). Although detailed analysis of purified stem versus progenitor populations has not been performed, these studies suggest that CBP may be necessary for proper HSC self-renewal during aging.…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 95%
“…Consistent with this assertion is the data provided by a third study, which found distinct roles for the two proteins, with CBP influencing HSC renewal and p300 influencing differentiation. 120 Interestingly, when the p300 doubleknockout HSCs were transplanted into WT animals, the differentiation defect was overcome, suggesting the intriguing possibility that the p300-deficient phenotype is influenced by the stroma rather than a HSC autonomous mechanism. 120 Given the wide range of roles that CBP and p300 play in the cell, it is perhaps not surprising that distinct facets of their biological roles are evident in different experimental systems.…”
Section: Differentiation Programs and The Transcriptomementioning
confidence: 99%
“…120 Interestingly, when the p300 doubleknockout HSCs were transplanted into WT animals, the differentiation defect was overcome, suggesting the intriguing possibility that the p300-deficient phenotype is influenced by the stroma rather than a HSC autonomous mechanism. 120 Given the wide range of roles that CBP and p300 play in the cell, it is perhaps not surprising that distinct facets of their biological roles are evident in different experimental systems. This example underscores the complexity of the functional response of even relatively homologous proteins and how subtle changes in the environment may dramatically change impact their effect.…”
Section: Differentiation Programs and The Transcriptomementioning
confidence: 99%